Why is the screening rate in lung cancer still low? A seven-country analysis of the factors affecting adoption - Poon, Charlotte; Wilsdon, Tim; Sarwar, Iqra; Roediger, Alexander; Yuan, Megan (Frontiers in Public Health, 2023)
Strong evidence of lung cancer screening's effectiveness in mortality reduction, as demonstrated in the National Lung Screening Trial (NLST) in the US and the Dutch-Belgian Randomized Lung Cancer Screening Trial (NELSON), has prompted countries to implement formal lung cancer screening programs. However, adoption rates remain largely low. This study aims to understand how lung cancer screening programs are currently performing. It also identifies the barriers and enablers contributing to adoption of lung cancer screening across 10 case study countries: